Selected advanced imaging techniques were unable to quantify in vivo parasitic burden in heartworm‐infested dogs. Issue 4 (22nd December 2020) - Lerer, Assaf; Bowman, Dwight D.; Luh, Wen‐Ming; Ohmes, Cameon M.; Scrivani, Peter V.
Abstract: This prospective exploratory study aimed to determine whether certain noninvasive advanced imaging techniques could estimate parasitic burden in heartworm‐infested dogs; a noninvasive method is needed for ethical considerations and permitting longitudinal drug studies. Three cardiac‐gated and respiratory‐gated 3T MRI techniques and CT pulmonary angiography (CTPA) were performed in three healthy beagles to optimize imaging techniques. Once the imaging techniques were established, a pilot study was performed to determine which one of the MRI techniques would be used in an observer comparison study. Ultimately, spoiled gradient recalled (SPGR)‐cine‐MRI and CTPA were performed in four and five heartworm‐infested dogs, respectively. Heartworms were detected in the pulmonary arteries in all dogs during SPGR‐cine‐MRI and in no dog during CTPA. However, counting the number of worms was unsuccessful. In conclusion, CTPA and SPGR‐cine‐MRI were unable to replace necropsy for quantifying parasitic burden in heartworm‐infested dogs.